Determinación del nivel de contaminación biológica por coliformes fecales en acuíferos no confinados (pozos) de uso para consumo humano - Torres Palomino, William (2014)
From decades ago the unconfined aquifers in Moyobamba city are used to supply water for the inhabitants located on the periphery of the Moyobamba city which make use of the resource for their daily actívíties in personal hygiene, laundry, and direct human consumption wíthout making any pre-treatment to treat ínfectious agents such as coliforms. Through this research work was able to determine the degree of contamination by total and fecal Coliforms of these unconfined aquifers; thís monitored 04 aquifers of 5 existing operational, by time of 4 consecutiva months with samples of each thirty (30) days. For the location of the stations to monitor took into account the target population, use frequency, for direct human consumption, houses presence in the surrounding area, lack of service of potable water and public sewer system. As a result of averages equivalent of the Monitoring of Total Coliforms of aquifers is evaluated of 1744.8875 NTC/100 mi exceeding the standards of water quality in Total Coliforms for human consumption with disinfection of 50 NMP/ml established by Suprema Decree No 002-2008-MINAM; as regards to fecal coliforms in 46.3125 NTC/ 100ml exceeding Water Quality Standards in Total Coliforms for human consumption with disinfection of 00 MPN/ml. The aquifer with the highest concentration of average equivalent is located in the Tipiníllo sector with 5165 NTC/100ml of Total Coliforms and 140 NTC/100 mi of fecal coliforms; these results indicate that the aquifers are not fit for human consumption in a straightforward manner, which could trigger in the generation of diseases spending-intestinal, skin etc. lts high concentration in both parameters evaluated, is mainly due to the high parts and the surrounding area are being populated which for the treatment of excreta built bathrooms dry without any medical treatment that ensures its ímperviousness to prevent contamination of underground aquifers, and in addition are places where it is not possible, the construction of a public sewage system for the treatment of wastewater and excretad by the fragility of the soil. Key words: unconfined aquifers, Total Coliforms